Saving Sammy : curing the boy who caught OCD - Maloney, Beth Alison (Crown Pub., 2009)
The summer before entering sixth grade, Sammy, a bright and charming boy, suddenly began to exhibit disturbing behaviors. His mother, Beth, watched helplessly as her middle child descended into madness. Sammy was soon diagnosed with obsessive-compulsive disorder (OCD) and later with Tourette syndrome. Unwilling to accept the prognosis of lifelong mental illness and repeated hospitalizations, Beth fought to uncover the cause. Her quest took her to the center of the medical community's raging debate about whether mental illness can be caused by infection. Beth searched until she found two cutting-edge doctors who answered that question with a definitive yes. Together, they cured Sammy. This book is part manifesto, part medical mystery, but is finally the empowering story of a mother's determination to save her son--From publisher description.